National and subnational size estimation of female sex workers in Ghana 2020: Comparing 3-source capture-recapture with other approaches - Guure, C.; Dery, S.; Torpey, K.; et al. (PLOS ONE, 2021)
Background Key Population size estimation (PSE) is instrumental for HIV/STI preventive, treatment and care services planning, implementation and delivery. The objective was to estimate the overall population of female sex workers (FSW) in all the 16 regions of Ghana using different PSE methods. Method Mapping of venues and complete enumeration of seaters was conducted at the formative stage prior to the bio-behavioral survey (BBS). Three PSE methods were used to derive the size estimates of FSW in the 16 regions. These include: Capture-recapture (CRC), service multiplier and three-source capture recapture (3SCRC) methods. The final choice of the estimation method used to estimate the roamer population was 3SCRC. This method was chosen because of its perfect record-linkage–hierarchic combination of three names that minimizes overmatching as well as the addition of an interaction term in the model which corrects for the dependencies in CRC. Results The total population size estimate of the female sex workers in the country obtained for roamers using capture re-capture was 41,746 (95% CI: 41,488–41,932). Using the service multiplier, the total population for both the roamers and seaters was 41,153 (95% CI: 37,242–45,984). The 3-source capture re-capture yielded 55,686 roamers FSW (95% CI: 47,686–63,686). The seater population was 4,363 FSW based on census/complete enu meration. The total population size estimate of FSW (seaters and roamers) in Ghana was 60,049 when 3SCRC and census were added. This represents about 0.76% of all estimated adult females aged 15-49yrs in Ghana. Conclusion We report population size estimates (PSE) for FSW in Ghana. These estimates are the results of 3SCRC. These findings provide a valid and reliable source of information that should be referenced by government officials and policymakers to plan, implement and pro vide HIV/STI preventive, treatment, and care services for FSW in Ghana.
Research Article
Keywords: female sex workers; Ghana; 3-source capture-recapture; HIV/STI